MiRNAs: Emerging Agents for Therapeutic Effects of Polyphenols on Ovarian Cancer - Badehnoosh, Bita; Rajabpoor Nikoo, Nesa; Asemi, Reza; Shafabakhsh, Rana; Asemi, Zatollah (Mini reviews in medicinal chemistry, 2024)
In terms of female reproductive tract cancers, ovarian cancer remains the principal reason for mortality globally and is notably difficult to identify in its early stages. This fact highlights the critical need to establish prevention strategies for patients with ovarian cancer, look for new robust diagnostic and prognostic markers, and identify potential targets of response to treatment. MicroRNAs (miRNAs) are one of the novel treatment targets in cancer treatment. Thus, understanding the part of miRNAs in the pathogenesis and metastasis of ovarian cancer is at the center of researchers' attention. MiRNAs are suggested to play a role in modulating many essential cancer processes, like cell proliferation, apoptosis, differentiation, adhesion, epithelial-mesenchymal transition (EMT), and invasion. In two recent decades, natural polyphenols' anti-cancer features have been a focal point of research. Meanwhile, polyphenols are good research subjects for developing new cancer treatments. Polyphenols can modify miRNA expression and impact the function of transcription factors when used as dietary supplements. Multiple works have indicated the impact of polyphenols, including quercetin, genistein, curcumin, and resveratrol, on miRNA expression and . Here, we provide an in-depth description of four polyphenols used as dietary supplements: quercetin, genistein, curcumin, and resveratrol, and we summarize what is currently known about their regulatory abilities on influencing the miRNA functions in ovarian tumors to achieve therapeutic approaches.